2020
DOI: 10.3390/ijms21113910
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Carboxyl-Terminal Hydrolases (UCHs): Potential Mediators for Cancer and Neurodegeneration

Abstract: Emerging evidence suggests an inverse association between cancer and neurodegenerative diseases (NDD). Although phenotypically different, both diseases display a significant imbalance in the ubiquitination/deubiquitination processes. Therefore, we particularly investigated the expression of ubiquitin C-terminal hydrolases (UCHs: UCH-L1, UCH-L3, UCH-L5 and BAP1), a subfamily of deubiquitinating enzymes (DUBs), using publically available datasets (GTEx, TCGA) and observed altered expression of UCH-L1, UCH-L3, UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…However, the most relevant research on DUBs is in the field of cancer 33 , 34 , including lung, liver 35 , breast 36 , stomach 37 , colon 38 , prostate 39 and ovarian cancers 40 . In this area, the mechanisms of DUBs in different tumors are described, and their potential as cancer therapeutics has attracted attention.…”
Section: A Brief Account Of Dubsmentioning
confidence: 99%
“…However, the most relevant research on DUBs is in the field of cancer 33 , 34 , including lung, liver 35 , breast 36 , stomach 37 , colon 38 , prostate 39 and ovarian cancers 40 . In this area, the mechanisms of DUBs in different tumors are described, and their potential as cancer therapeutics has attracted attention.…”
Section: A Brief Account Of Dubsmentioning
confidence: 99%
“…There has been a constant search for identifying HCC-related biomarkers, however, most of them showed association with poor prognosis, either in early or advanced HCC [ 4 ]. Notably, two members of the ubiquitin C-terminal hydrolases (UCHs) family, BRCA1-associated protein-1 (BAP1) [ 5 ] and UCH-L3 [ 6 ] have been implicated in the survival rate of this particular cancer. More recently, authors established immuno-autophagy-related long non-coding RNA (IARlncRNA) signature with a prognostic ability in HCC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…No clear modifier or biochemical markers of progression have been identified, with the exception of a progressive decrease in dopaminergic cell function. A number of epidemiological studies have indicated an inverse association between the risk of developing malignancies and PD (except melanoma) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%